MEMBUMIKAN PLURALISME PERSPEKTIF ISLAM INDONESIA: FAKTA, TANTANGAN DAN GAGASAN - Mahathir Muhammad Iqbal (Nizham Jurnal Studi Keislaman, 2015)
Indonesia is a pluralistic nation. Both in terms of cultural entities, language, tribe, ethnic and religious differences. Therefore, the pluralism can not be understood simply by saying that our society is pluralistic, diverse, or made up of different tribes and religions, which is actually only describe the impression of fragmentation, not pluralism. Pluralism should also not be understood merely "negative goodness", which is seen usefulness to get rid of fanaticism. Instead, pluralism should be understood as a true affinity diversity in bundles politeness. Even, pluralism is a must for the salvation of mankind, including through mechanisms supervision and balances that result. In the Islamic perspective it is mentioned that God created the mechanism of checks and balances among humans in order to maintain the integrity of the earth, and is one manifestation of God's abundant mercy to mankind.